2009
DOI: 10.1148/radiol.2521081200
|View full text |Cite
|
Sign up to set email alerts
|

Locally Advanced Rectal Cancer: MR Imaging for Restaging after Neoadjuvant Radiation Therapy with Concomitant Chemotherapy Part I. Are We Able to Predict Tumor Confined to the Rectal Wall?

Abstract: Downsizing to ypT0-2 tumors can be accurately predicted by combining morphologic tumor staging predictions with results from volumetric analyses. MR images obtained after radiation therapy with concomitant chemotherapy might be helpful in more individualized treatment planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
67
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(79 citation statements)
references
References 45 publications
5
67
0
7
Order By: Relevance
“…Although standardised histological examination procedures were used and detailed pathology reports were provided by an experienced pathologist, exact matching between the MR images and histopathological findings for the viable tumour may have been suboptimal. Second, the percentage of complete histopathological responders in our study was 12%, a rate similar to that found by others [20,23,24,[42][43][44]. The small number of cases with pathological CR might, however, have led to overestimation of diagnostic accuracy.…”
supporting
confidence: 88%
“…Although standardised histological examination procedures were used and detailed pathology reports were provided by an experienced pathologist, exact matching between the MR images and histopathological findings for the viable tumour may have been suboptimal. Second, the percentage of complete histopathological responders in our study was 12%, a rate similar to that found by others [20,23,24,[42][43][44]. The small number of cases with pathological CR might, however, have led to overestimation of diagnostic accuracy.…”
supporting
confidence: 88%
“…Although tumor volumetry is an operator-dependent and time-consuming semiautomatic technique, the volumetric evaluation may have better accuracy and reproducibility than the classic approach of tumor diameter measurement (10). The accurate assessment of tumor volume reduction and downstaging might enable of a local excision or a nonsurgical approach to be considered in patients who have a good probability of anal sphincter preservation or a good tumor response after preoperative CRT (11,12). Researchers have reported that the tumor volume reduction rate is significantly correlated with the downstaging of locally advanced rectal cancer following preoperative CRT (13).…”
mentioning
confidence: 99%
“…При этом патоморфоз, выявляемый по моди-фицированной для МР-диагностики шкале Mandard, коррелировал с высокой точностью с патоморфоло-гическим заключением [15], что позволило внедрить выжидательную тактику с активным динамическим наблюдением в клиниках, имеющих в штате специа-листов рентгенодиагностики достаточной квалифика-ции. Следует отметить, что сложности диагностики полного клинического ответа отмечаются всеми авто-рами, изучающими данную проблему [16].…”
Section: Discussionunclassified